Counseling of balanced ration arrangement for fattening cows in Marga Agung Village, South Lampung - Farda, Fitria Tsani; Fathul, Farida; Erwanto, Erwanto; Hasiib, Etha Azizah (Community Empowerment, 2021)
The purpose of this service activity is to increase the knowledge and skills of breeders in Marga Agung Village, Jati Agung Subdistrict, South Lampung Regency regarding various types of forage, compiling ration formulations based on local feed, and processing feed from agricultural waste. The main issues that become priority are (1) the ability of breeders to prepare beef cattle feed rations; (2) utilization of feed processing technology to improve the nutritional quality of animal feed; and (3) livestock businesses that have not been able to boost the farmer economy. Through the Participatory Rural Appraisal method, this activity was able to increase the knowledge and skills of breeders in preparing local feed-based ration formulations and processing feed from agricultural waste.